Midwives' Compliance With The Use Of Personal Protective Equipment In Efforts To Prevent Post-Covid-19 In The Klinik Mandiri Bidan Setia Palu City - Jufri, Muhammad; Amalinda, Finta; Hardianti, Sri (HUMANUS : Jurnal Sosiohumaniora Nusantara, 2023)
Personal protective equipment (PPE) must be used to avoid work accidents. Midwives have a considerable risk of contracting the disease because midwives have contact with the body fluids of pregnant/mother who gives birth, such as blood and amniotic fluid. The purpose of this research was to determine the compliance of midwives with the use of personal protective equipment in efforts to prevent post-COVID-19 in the Klinik Mandiri Bidan Setia Palu City. This research employs a type of research with a qualitative approach. The number of informants is five informants. The data was collected through in-depth interviews, direct observation, and documentation. The results of this research show that midwives are cheerful and obedient in using personal protective equipment. Midwives have a positive attitude toward using personal protective equipment because PPE is the need of every individual and must be obeyed for the benefit of all. According to Standard Operating Procedure, midwives comply with personal protective equipment. It is recommended that midwives in The Klinik Mandiri Bidan Setia Palu city  always increase awareness of the disease by using complete PPE.